Pemberdayaan masyarakat dalam mengolah produk makanan berbahan dasar lokal di Kabupaten Sidrap - Hermawati Hermawati; Tamrin Mallawangeng (DEDIKASI, 2019)
One of the natural potentials available in large quantities in the Tanete Village is the chicken farming sector. Efforts to empower the community of Tanete Village can be done by promoting appropriate technology. Food processing technology based on chicken meat is in the form of meatballs, sausages, jerky and crispy chicken skin crackers. The processed products are animal origin foods which are processed with the aim to have a longer shelf life and add flavor to the menu or daily dishes. Through this diversification the shelf life can reach more than 60 days. The purpose of the Community Partnership Program (PKM) is to change the mindset of housewives to be more creative in diversifying processed products from the local potential available in their villages, so as to be able to contribute greatly to the family economy.